The Liberal Education of Charles Eliot Norton - Turner, James C. (Johns Hopkins University Press, 1999)
James Turner's biography offers the first modern account of Norton's life and its significance, following him from his perilous travels across India as a young merchant to his role as his country's preeminent cultural critic. Turner shows how Norton developed the key ideas that still underlie the humanities-historicism and culture-and how his influence endures in America's colleges and universities because of institutions he developed and models he devised.